Poly(lactic acid)/poly(ethylene glycol) polymer nanocomposites: effects of graphene nanoplatelets - Chieng, Buong Woei; Ibrahim, Nor Azowa; Wan Yunus, Wan Md. Zin; Hussein, Mohd Zobir (MDPI, 2014)
Graphene nanoplatelets (xGnP) were investigated as a novel nano-reinforcement filler in poly(lactic acid)(PLA)/poly(ethylene glycol)(PEG) blends by the melt blending method. PLA was first plasticized by PEG in order to improve its flexibility and thereby overcome its problem of brittleness. Then, xGnP was incorporated into the PLA/PEG blend. The prepared nanocomposites exhibited a significant improvement in tensile properties at a low xGnP loading. The tensile properties demonstrated the addition of 0.3 wt% of xGnP led to an increase of up to 32.7%, 69.5% and 21.9% in tensile strength, tensile modulus and elongation at break of the nanocomposites respectively, compared to PLA/PEG blend. X-ray diffraction (XRD) patterns showed the presence of a peak around 26.5○ in PLA/PEG/xGnP nanocomposites which corresponds to the characteristic peak of xGnP. The nanocomposites also shows enhanced thermal stability compared with PLA/PEG blend in thermogravimetry analysis (TGA). The enhancement to some extent of the tensile properties of the PLA/PEG/xGnP nanocomposites can be ascribed to the homogeneous dispersion and orientation of the xGnP nanoplatelets in the polymer matrix and strong interfacial interaction between both components. The scanning electron microscopy (SEM) image of PLA/PEG/0.3 wt% xGnP displays good uniformity and more homogenous morphology. Good uniformity of composites indicates a good degree of dispersion of the xGnp and therefore results in good tensile and thermal properties.